The Use of Protease Inhibitors in Pregnancy: Maternal and Fetal Considerations - Elaine Duryea; Fiona Nicholson; Sara Cooper; Scott Roberts; Vanessa Rogers; Donald McIntire; Jeanne Sheffield; Robert Stewart (Hindawi Limited, 2015)
Background. Previous studies examining protease inhibitor use in pregnancy and the rate of preterm and small-for-gestational-age infants have yielded conflicting results. Methods. This was a retrospective study of HIV-infected women who delivered singleton infants at our institution between 1984 and 2014. Women with protease inhibitor use were compared to women on regimens without a protease inhibitor as well as those who received no antepartum antiretroviral therapy. Infants were considered preterm if less than 37 completed weeks of gestation and small-for-gestational-age if less than 10th percentile. Results. During the study period 1,004 pregnancies met inclusion criteria. Of those, 597 received a protease inhibitor as part of their regimen, 230 ART without a protease inhibitor, and 177 no ART. There was no difference in the rate of preterm birth between groups who received ART with or without a protease inhibitor, 14% versus 13%. There was no difference in the rate of small-for-gestational-age infants between the three groups. Use of a protease inhibitor was associated with a greater fall in viral load during pregnancy, p<0.001. Conclusion. In this population with access to prenatal care and ART, treatment with protease inhibitors was associated with a greater fall in viral load, but not an increase in small or preterm infants.